Workforce Serving Pregnant and Postpartum Medicaid Enrollees at Community Health Centers, 2016 to 2021 - Mandar Bodas; Yoon Hong Park; Qian (Eric) Luo; Anushree Vichare (Journal of Primary Care & Community Health)
Introduction: Community Health Centers (CHCs) care for nearly a third of all pregnant Medicaid enrollees. Given that Medicaid covers 41% of childbirths, CHCs play a critical role in ensuring pregnant enrollees’ access to perinatal services. Despite their importance, little is known about the CHC workforce serving these patients. This study uses multi-state Medicaid claims data to analyze the providers caring for pregnant Medicaid enrollees at CHCs. Methods: Our primary data source was the Transformed Medicaid Statistical Information System (T-MSIS) Analytical File (TAF), 2016 to 2021. We identified all pregnant and postpartum Medicaid enrollees that received care at CHCs and examined the workforce serving this population from the following specialties: Obstetricians and Gynecologists (OBGYNs), Nurse Practitioners (NPs), Family Physicians (FPs), and Physician Associates (PAs). We summarized the annual number of providers from each specialty and total number of pregnant and postpartum enrollees served per year. Since the study period overlapped with the COVID-19 pandemic, we also examined the provision of telehealth by this workforce. Results: The workforce serving pregnant Medicaid enrollees at CHCs each year grew 23% during the study period (22 027-28 668 providers), and that serving postpartum enrollees increased by 20% (25 655-32 026). Total annual number of NPs experienced faster growth than FPs for both pregnant (31% vs 17%) and postpartum enrollee care (27% vs 17%). OBGYN and PA counts remained relatively stable during the study period. The number of providers that served pregnant and postpartum Medicaid enrollees via telehealth peaked in April 2020. Each year, OBGYNs served about 140 pregnant enrollees per provider, compared to 30 for FPs, 20 for NPs, and 10 for PAs . Similarly, the average number of postpartum enrollees served was steady during the study period: OBGYNs served around 70, FPs 20, and both NPs and PAs approximately 10 postpartum enrollees each year. Discussion: This unique analysis of data from Medicaid claims showed growth in the CHC perinatal workforce and highlighted the role played by providers from certain specialties and professions in caring for pregnant Medicaid enrollees. Policymakers could leverage these findings to design targeted investments for high-impact provider groups within the CHC perinatal workforce.